Phenotypic and Genetic Evolutions of a Porcine Reproductive and Respiratory Syndrome Modified Live Vaccine after Limited Passages in Pigs - Eclercy, Julie (Vaccines (Basel), 2021)
Modified live vaccines (MLVs) against the porcine reproductive and respiratory syndrome virus (PRRSV) have been regularly associated with safety issues, such as reversion to virulence. In order to characterize the phenotypic and genetic evolution of the PRRSV-1 DV strain from the Porcilis(®) PRRS MLV after limited passages in pigs, three in vivo experiments were performed. Trial#1 aimed (i) at studying transmission of the vaccine strain from vaccinated to unvaccinated contact pigs. Trial#2 and Trial#3 were designed (ii) to assess the reproducibility of Trial#1, using another vaccine batch, and (iii) to compare the virulence levels of two DV strains isolated from vaccinated (passage one) and diseased contact pigs (passage two) from Trial#1. DV strain isolates from vaccinated and contact pigs from Trial#1 and Trial#2 were submitted to Next-Generation Sequencing (NGS) full-genome sequencing. All contact animals from Trial#1 were infected and showed significantly increased viremia compared to vaccinated pigs, whereas no such change was observed during Trial#2. In Trial#3, viremia and transmission were higher for inoculated pigs with passage two of the DV strain, compared with passage one. In this study, we showed that the re-adaptation of the DV strain to pigs is associated with faster replication and increased transmission of the vaccine strain. Punctually, a decrease of attenuation of the DV vaccine strain associated with clinical signs and increased viremia may occur after limited passages in pigs. Furthermore, we identified three mutations linked to pig re-adaptation and five other mutations as potential virulence determinants.